The University in the Service of Professional Settings - Nesba, Asma; GHEDEIR BRAHIM, Mohammed (University of eloued جامعة الوادي, 2017)
Policymakers are aware of the importance of introducing English as an ESP module in different specialties in the Algerian universities. However, in the workplace, university degree holders encounter difficulties to accomplish Language-related tasks. A study was conducted then to find out the cause of the gap existing between the university and the workplace for an ultimate goal to find solutions to bridge the gap between the university and the real work context by helping new recruited workers to exploit their previous language knowledge in professional settings. The study was conducted in a private language school in a class of eight (08) adult learners receiving intensive instruction in Business English. 02 businessmen and 06 sales managers in private companies. A questionnaire was used as data gathering tool to detect their motives to have such courses. Results reveal that their resort to ESP sessions in private schools is due to their failure to exploit their language knowledge to solve practical problems in the workplace especially problems related to business correspondence . Results led to the construction of pedagogical implications that highlight the importance of ESP and languages for specific purposes in general in equipping the present university students, the future workers, with the required language skills that will satisfy the professional settings needs. Recommendations focus on the necessity of having qualified and well trained ESP teachers at the department of Economy and Management as well as building a continuum between university and the professional settings.
Colloque International Langues, Employabilité et Enseignement Supérieur - جامعة وهران2
Keywords: Business Communication; Business correspondence; Emailing; ESP; Language-related tasks, Professional Settings.